Histopathology and ultrastructural features in mucous extravasation phenomenon: Report of a case - B. T Shareef; Karima Al-Salihi; A. R Samsudin; A. Pohchi (Universidade Estadual de Campinas, 2015)
Histopathological and ultrastructural features of a case of pseudocyst extravastation mucocele lesion located in the lower lip of an 18 yearold Malaysian female is presented. Complete surgical excision of the lesion with associated minor salivary glands was done. The specimen was processed for routine histopathology and transmission electron microscopy (TEM) for ultrastructral studies. The lesion revealed pooling of mucin infiltrated with inflammatory cells and walled by a rim of granulation tissue. The underlying salivary lobules showed varying degrees of chronic sclerosing sialadenitis. Ultrastructural features revealed multiple membrane bound electron lucent mucus granules with varying diameter, duct cells with few microvilli. Desmosomes, tonofilaments and myoepithelial cells were prominent. There were also dilatation of the rough endoplasmic reticulum (RER) and presence of multiple electron dense granules